ABOUT THE AGE OF ALISHER NAVOIY ISKANDAR (Analysis of stories) - Shodiya Otanazarova (Journal of Learning on History and Social Sciences, 2024)
Alisher Navoi tried to get as close as possible to the historical roots of the image of Alexander the Great in his work. While interpreting the image of Iskandar from different perspectives, Navoi always tries to be careful of mistakes and, as much as possible, he achieves that his artistic interpretations of the image he portrays are consistent with historical reality